2017
DOI: 10.1123/ijsnem.2016-0239
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Dietary Nitrate Intake in Highly Trained Athletes

Abstract: Although beetroot juice, as a nitrate carrier, is a popular ergogenic supplement among athletes, nitrate is consumed through the regular diet as well. We aimed to assess the habitual dietary nitrate intake and identify the main contributing food sources in a large group of highly trained athletes. Dutch highly trained athletes (226 women and 327 men) completed 2-4 web-based 24-hr dietary recalls and questionnaires within a 2-to 4-week period. The nitrate content of food products and food groups was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 29 publications
4
23
1
Order By: Relevance
“…In turn, the consistent finding of higher NO − 3 plasma levels in endurance athletes relative to less trained individuals 11,[29][30][31] which was also observed in the present study, and the general lack of effect from NO − 3 supplementation in endurance athletes 7-12 could be speculated to relate to higher NOS content 5 and/or higher daily dietary intake of NO − 3 due to increased energy intake. 35 There is evidence to suggest that a NO − 3 dose and physiologic response relationship exists; 34 however, the NO − 3 dose used in the present study (9 mmol) is similar to or higher than the doses used in previous studies reporting significant effects on energy expenditure and blood pressure following an acute dose in moderately trained subjects 16 and kayakers. 36,37 Furthermore, a quite large dose (19.5 mmol) 8 failed to lower submaximal VO 2 in highly trained runners indicating that subjects not responsive to NO − 3 supplementation, similar to those in the present study, will not benefit from a more aggressive supplementation strategy.…”
Section: Discussionsupporting
confidence: 42%
“…In turn, the consistent finding of higher NO − 3 plasma levels in endurance athletes relative to less trained individuals 11,[29][30][31] which was also observed in the present study, and the general lack of effect from NO − 3 supplementation in endurance athletes 7-12 could be speculated to relate to higher NOS content 5 and/or higher daily dietary intake of NO − 3 due to increased energy intake. 35 There is evidence to suggest that a NO − 3 dose and physiologic response relationship exists; 34 however, the NO − 3 dose used in the present study (9 mmol) is similar to or higher than the doses used in previous studies reporting significant effects on energy expenditure and blood pressure following an acute dose in moderately trained subjects 16 and kayakers. 36,37 Furthermore, a quite large dose (19.5 mmol) 8 failed to lower submaximal VO 2 in highly trained runners indicating that subjects not responsive to NO − 3 supplementation, similar to those in the present study, will not benefit from a more aggressive supplementation strategy.…”
Section: Discussionsupporting
confidence: 42%
“…The study was performed between February 2012 and June 2015 as described by Wardenaar et al [ 24 ] and others [ 25 , 26 ]. A total of 1800 athletes were informed about the study.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is important to consider the possibility that non-sex-specific differences may be driving these responses. For example, Jonvik et al (2016) found that highly trained females had greater dietary NO 3 intake compared with males. Furthermore, little is known regarding differences in other dietary and lifestyle factors that may influence plasma NO 3 and NO 2 levels.…”
Section: Supplemental No 3 Dose-response and Pharmacokineticsmentioning
confidence: 99%